This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Granillo, Yvette – Review 3 – Due: Dec 9 2005, 6:00 pm – Inst: Edward Odell 1 This printout should have 18 questions. Multiplechoice questions may continue on the next column or page – find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points If f 1 is the inverse of f , determine the value of f ( f 1 (9)). 1. f ( f 1 (9)) = 1 9 2. f ( f 1 (9)) = 9 correct 3. f ( f 1 (9)) = 81 4. Need to know f 5. f ( f 1 (9)) = 1 81 Explanation: The inverse, f 1 , of f has the property that f ( f 1 ( x )) = x, f 1 ( f ( x )) = x. Consequently, f ( f 1 (9)) = 9 . keywords: Stewart5e, 002 (part 1 of 1) 10 points Find the inverse function, f 1 , of f when f is defined by f ( x ) = √ 7 x 5 , x ≥ 5 7 . 1. f 1 ( x ) = 1 7 ( x 2 + 5) , x ≥ 7 5 2. f 1 ( x ) = 1 5 p x 2 + 7 , x ≥ 7 5 3. f 1 ( x ) = 1 7 ( x 2 + 5) , x ≥ correct 4. f 1 ( x ) = 1 7 p x 2 5 , x ≥ 5. f 1 ( x ) = 1 5 ( x 2 7) , x ≥ 5 7 6. f 1 ( x ) = 1 5 p x 2 7 , x ≥ Explanation: Since f has domain [ 5 7 , ∞ ) and is increasing on its domain, the inverse of f exists and has range [ 5 7 , ∞ ); furthermore, since f has range [0 , ∞ ), the inverse of f has domain [0 , ∞ ). To determine f 1 we solve for x in y = √ 7 x 5 and then interchange x, y . Solving first for x , we see that 7 x = y 2 + 5 . Consequently, f 1 is defined on [0 , ∞ ) by f 1 ( x ) = 1 7 ( x 2 + 5) . keywords: Stewart5e, 003 (part 1 of 1) 10 points Find the value of g ( 1) when g is the inverse of the function f defined by f ( x ) = 2 x 3 3 x . ( Hint : f (1) = 1.) 1. g ( 1) = 2 2. g ( 1) = 1 9 correct 3. g ( 1) = 1 9 4. g ( 1) = 2 5. g ( 1) = 9 Granillo, Yvette – Review 3 – Due: Dec 9 2005, 6:00 pm – Inst: Edward Odell 2 6. g ( 1) = 9 Explanation: When g is the inverse of f then f ( g ( x )) = x, so f ( g ( x )) g ( x ) = 1 , i.e. , g ( x ) = 1 f ( g ( x )) . But, if f ( x ) = 2 x 3 3 x , we know that f ( x ) = 6 x 2 + 3 x 2 , f (1) = 1 ; in particular, g ( 1) = 1 and f (1) = 9 . Consequently, g ( 1) = 1 f (1) = 1 9 . keywords: Stewart5e, 004 (part 1 of 1) 10 points Find f ( x ) when f ( x ) = 9 cos x 8 sin x and f (0) = 3. 1. f ( x ) = 9 sin x + 8 cos x 6 2. f ( x ) = 9 cos x + 8 sin x 6 3. f ( x ) = 9 cos x + 8 sin x + 12 4. f ( x ) = 9 cos x + 8 sin x + 12 5. f ( x ) = 9 sin x + 8 cos x 5 6. f ( x ) = 9 sin x + 8 cos x 5 correct Explanation: Since d dx sin x = cos x, d dx cos x = sin x, we see immediately that f ( x ) = 9 sin x + 8 cos x + C with C an arbitrary constant. The condition f (0) = 3 determines C : f (0) = 3...
View
Full
Document
This test prep was uploaded on 04/16/2008 for the course M 408k taught by Professor Schultz during the Spring '08 term at University of Texas at Austin.
 Spring '08
 schultz

Click to edit the document details